At the 1915 Fair - Frederick V. Bowers::::::::: (Frederick V. Bowers Publishing Co.)
Piano score, 6 p. On cover: To Miss Martha Dieterichfairest daughter of the fairest state., Also on cover is port. of Miss Martha Dieterich, queen of the Los Angeles Fire Department. Port. of composer on verso of last leaf.